2005
DOI: 10.2105/ajph.2004.045898
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of School Programs in Preventing Childhood Obesity: A Multilevel Comparison

Abstract: Our finding that school programs are effective in preventing childhood obesity supports the need for broader implementation of successful programs, which will reduce childhood obesity and, in the longer term, comorbid conditions and health care spending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
239
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(264 citation statements)
references
References 23 publications
15
239
1
9
Order By: Relevance
“…The differences in HRQOL outcomes by diet quality specifically Table 2 Associations of diet quality, physical activity, body weight status and sociodemographic factors with VAS score*: grade 5 students aged 10-11 years (n 3421), Alberta, Canada, 2008 suggest the importance of nutrition programmes focusing on improving diet quality among children in the development of school health promotion. One Canadian study has shown that nutrition programmes that are based on comprehensive school health exhibit a greater positive effect on students' diets, PA and overweight reduction than a single nutrition programme (13) . More research is needed to examine whether such comprehensive school health approaches that integrate nutrition education, nutrition policy, healthy food services, environmental support and various PA strategies into a whole school model will result in an improvement of HRQOL among children.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in HRQOL outcomes by diet quality specifically Table 2 Associations of diet quality, physical activity, body weight status and sociodemographic factors with VAS score*: grade 5 students aged 10-11 years (n 3421), Alberta, Canada, 2008 suggest the importance of nutrition programmes focusing on improving diet quality among children in the development of school health promotion. One Canadian study has shown that nutrition programmes that are based on comprehensive school health exhibit a greater positive effect on students' diets, PA and overweight reduction than a single nutrition programme (13) . More research is needed to examine whether such comprehensive school health approaches that integrate nutrition education, nutrition policy, healthy food services, environmental support and various PA strategies into a whole school model will result in an improvement of HRQOL among children.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (11) , however, it was observed that private school students consumed more high-calorie foods while at school, such as: soft drinks, fried foods, and candies. Nonetheless, in another line of thought, but also considering the effect of school environment on the development of O/O, there is evidence (14) that well-structured campaigns can significantly reduce O/O prevalence and physical inactivity among those students.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several systematic reviews of childhood obesity programs have been published. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] With the exception of one recent review 20 and an earlier review conducted by our team in collaboration with the Community Guide Branch of the Center for Disease Control and Prevention (CDC), 25 this work is unique in that it focuses specifically on studies undertaken in schools. Previous reviews have focused solely on the prevention of obesity 22 or weight loss interventions among already overweight children.…”
Section: Introductionmentioning
confidence: 99%